2007
DOI: 10.1590/s0034-70942007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia de parto: estudo comparativo entre anestesia combinada raquiperidural versus anestesia peridural contínua

Abstract: JUSTIFICATIVA E OBJETIVOS:O alívio da dor no trabalho de parto tem recebido atenção constante visando ao bem-estar materno, diminuindo o estresse causado pela dor e reduzindo as conseqüên-cias deste sobre o concepto. Inúmeras técnicas podem ser utilizadas para analgesia de parto. Este trabalho teve como objetivo comparar a técnica peridural contínua com a combinada, ambas com o uso de bupivacaína a 0,25% em excesso enantiomérico 50% e fentanil como agentes. MÉTODO:Participaram do estudo 40 parturientes em trab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 15 publications
0
4
0
12
Order By: Relevance
“…Cerca de 30% (12) dos partos foram fórceps e 12,5% (5) foram cesárea. Os autores justificaram o número alto de fórceps como uma conduta obstétrica do hospital onde o estudo foi realizado (16) .…”
Section: Discussionunclassified
“…Cerca de 30% (12) dos partos foram fórceps e 12,5% (5) foram cesárea. Os autores justificaram o número alto de fórceps como uma conduta obstétrica do hospital onde o estudo foi realizado (16) .…”
Section: Discussionunclassified
“…Spinal anesthesia performed with fine gauge disposable needles and administration of bupivacaine combined with adjuvant drugs into the subarachnoid space, is reported as effective technique in most caesarean sections [20][21][22]. Previous studies have indicated that administration of epidural bupivacaine in labor analgesia is an advantage because it is coupled with lower intensity of motor blockade [23,24] besides preserving the differential blockade of racemic bupivacaine [25][26][27][28]. The aim of this perspective, double blind randomized study was to evaluate and compare the effectiveness of bupivacaine-fentanyl, bupivacaineclonidine and bupivacaine-dexmetomodine on the quality of blockade and maternal and neonatal repercussions.…”
mentioning
confidence: 99%
“…As an advantage, anesthesia ensures that the pregnant woman remains collaborative and prevents excessive maternal hyperventilation and its consequences for the fetus, such as metabolic acidosis, and bradycardia 6 . Other advantages are the decrease in anxiety, the increase in uterine blood flow and placental intervillous spaces, the regularization of contractions, and greater hemodynamic stability during labor 15,16 .…”
Section: Discussionmentioning
confidence: 99%